2009
DOI: 10.1111/j.1467-8500.2009.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Public Accountability: The ‘Wenling Model’ in China

Abstract: This article specifically attempts to answer two interrelated research questions: firstly, how do democratic consultation assemblies (DCAs) heighten public accountability in the current institutional setting of China's sub-provincial localities?; and secondly, what can be learned, from the Chinese case, in relation to achieving public accountability elsewhere? To address the first question, this article will explore two particular variations of the DCAs, and will focus on the interplay between the managerial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
5
0
3
Order By: Relevance
“…12 The monitoring can also be strengthened by utilizing increasingly assertive congresses to exercise a check over intermediate governments. In a study of public accountability in Zhejiang Province in China, Hsu (2009) (Guo, 2008). Improving fiscal capacity at the local level thus is imperative in China.…”
mentioning
confidence: 99%
“…12 The monitoring can also be strengthened by utilizing increasingly assertive congresses to exercise a check over intermediate governments. In a study of public accountability in Zhejiang Province in China, Hsu (2009) (Guo, 2008). Improving fiscal capacity at the local level thus is imperative in China.…”
mentioning
confidence: 99%
“…Literature has shown that in many cases these people's opinions on given public issues changed significantly before and after the process. The method has been applied successfully even in authoritarian societies (see the experiences in the PRC, called "authoritarian deliberation" by He and Warren, 2011; see also Fishkin et al, 2010;He and Hundt, 2011;Hsu, 2009). For the description of the other models, see the survey in Smith (2011).…”
Section: Notesmentioning
confidence: 98%
“…China’s governance style has gradually changed to a more consultative and less top‐down approach over the past 10 years. At the same time, a strict accountability system has been established since the SARS epidemic (Cai & Zhu, ; Hsu, ; Ma, ). The accountability system forces political leaders or bureaucrats to respond quickly to resolve existing problems, or they may be held accountable and lose their positions.…”
Section: The Policy Process and Governance In Transitional Chinamentioning
confidence: 99%